Surface charge and particle size determine the metabolic fate of dendritic polyglycerols. Issue 25 (15th June 2017) - Pant, Kritee; Pufe, Johanna; Zarschler, Kristof; Bergmann, Ralf; Steinbach, Jörg; Reimann, Sabine; Haag, Rainer; Pietzsch, Jens; Stephan, Holger
Abstract : Dendritic polyglycerols (dPG) are water soluble, polyether-based nanomaterials which hold great potential in diagnostic as well as therapeutic applications. Abstract : Dendritic polyglycerols (dPG) are water soluble, polyether-based nanomaterials which hold great potential in diagnostic as well as therapeutic applications. In order to translate them for in vivo applications, a systematic assessment regarding their cell and tissue interactions as well as their metabolic fate in vivo is a crucial step. Herein, we explore the structure–activity relationship of three different sizes ( ca. 3, 5, and 10 nm) of neutral dendritic polyglycerol (dPG) and their corresponding negatively charged sulfate analogs (dPGS) on their in vitro and in vivo characteristics. Cellular metabolic activity was studied in A431 and HEK293 cells. Biomolecular corona formation was determined using an electrophoretic mobility shift assay, which showed an increased protein binding of the dPGS even with serum concentrations as low as 20%. An in situ technique, microscale thermophoresis, was employed to address the binding affinities of these nanomaterials with serum proteins such as serum albumin, apo-transferrin, and fibrinogen. In addition, nanoparticle–cell interactions were studied in differentiated THP-1 cells which showed a charge dependent scavenger receptor-mediated uptake. In line with this data, detailed biodistribution and small animal PET imaging studies in Wistar rats using 68 Ga-labeled dPG-/dPGS-NOTA conjugates showed that the neutral dPG-NOTA conjugates were quantitatively excreted via the kidneys with a subsequent hepatobiliary excretion with an increase in their size, whereas the polysulfated analogs (dPGS-NOTA) were sequestered preferentially in the liver and kidneys irrespective of their size. Taken together, this systematic study accentuates that the pharmacokinetics of dPGs is critically dependent on the overall size and charge and can be, fine-tuned for the intended requirements in nano-theranostics.